Determination of Vibration Borne Stress in a Pipeline Using Fluid Structure Interaction - Abdul Ghaffar, Abdul Rahman (2013)
Excessive vibration is one of the leading causes of high cycle fatigue in process piping. Conventional way to assess the severity of vibration is to measure the stress caused by vibration with strain gages. An alternative way is discussed in this paper. The basis of this alternative way was formed by Operational Deflection Shape (ODS) analysis. In order to test the method, ODS was measured from a dual spiral system piping system which was a highly pressurized gas transporting pipeline in an offshore platform. Modal parameter such as natural frequency and mode shape were extracted from the result of ODS analysis and the modal parameter was used to correlate and verify a finite element (FE) model. Given the operating condition of the flow in the pipe, Fluid-Structure Interaction (FSI) was then performed where structural and fluid were fully coupled. From the FSI analysis, vibration-induced stress was estimated and the risk of fatigue failure of piping system can be concluded by comparing with allowable endurance limit of piping material.